Institutional Repositories serve the interests of research funders - Havemann, Jo (My University, 2024)
Presentation held at the Africa PID Alliance (africapidalliance.org) Webinar: How effective FAIR data management aids in the visibility of African funding output "Effective FAIR data management significantly aids in the visibility of African funding outputs by making research more discoverable, accessible, interoperable, and reusable. This not only boosts the profile of African research on the global stage but also fosters collaborations, enhances credibility, informs policy, and attracts further funding. For more on how we have been doing this please join our partners Crossref and Research Organization Registry(ROR) as we take you through what we have been doing and listen to some of the African funders case studies from National Research Fund Kenya and National de la Recherche et de l’Innovation pour le Développement - FONRID (Burkina Faso) in addition with the contributions from Association of African Universities and African Open Science Platform who will share the research management and policy-making implications on making African funders output accessible." Watch the recording at https://doi.org/10.21428/359fb1d2.0361a9d0
Keywords: AfricArXiv; Funding; Research in Africa; FAIR Principles; Persistent Identifiers